2013
DOI: 10.1371/journal.pone.0082781
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Polymorphism in the 5HTR2C Gene Associated with Stress Responses Also Predicts Incident Cardiovascular Events

Abstract: Previously we have shown that a functional nonsynonymous single nucleotide polymorphism (rs6318) of the 5HTR2C gene located on the X-chromosome is associated with hypothalamic-pituitary-adrenal axis response to a stress recall task, and with endophenotypes associated with cardiovascular disease (CVD). These findings suggest that individuals carrying the rs6318 Ser23 C allele will be at higher risk for CVD compared to Cys23 G allele carriers. The present study examined allelic variation in rs6318 as a predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
5
15
0
2
Order By: Relevance
“…The present findings, along with studies linking the Ser23 C allele with affective disorders, also suggest that the rs6318 effects on HT2C receptor-mediated effects on emotion and the HPA axis may moderate, at least in part, the linkages between depression and dysregulated HPA axis function. In addition, the present findings also may point to a mechanism underlying the association we previously reported between Ser23 C and incidence of death or MI in a large CHD patient sample(Brummett, et al, 2013). …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The present findings, along with studies linking the Ser23 C allele with affective disorders, also suggest that the rs6318 effects on HT2C receptor-mediated effects on emotion and the HPA axis may moderate, at least in part, the linkages between depression and dysregulated HPA axis function. In addition, the present findings also may point to a mechanism underlying the association we previously reported between Ser23 C and incidence of death or MI in a large CHD patient sample(Brummett, et al, 2013). …”
Section: Discussionsupporting
confidence: 76%
“…This prior study, however, consisted of males only. In related recent study of 6,126 men and women referred for diagnostic cardiac catheterization, we also showed that over a 7-year follow-up period, males hemizygous for Ser23 C and females homozygous for Ser23 C allele had an increase in cardiovascular disease event (death and/or MI) risk (hazard ratio = 1.38) compared to those with other rs6318 genotypes (Brummett et al, 2013). One possible mechanism that might explain the increased prognostic risk associated with Ser23C might be the tendency to respond to psychological stress during daily life with heightened HPA-axis activity, which, over time is thought to promote atherogenesis (Rozanski, Blumenthal, Davidson, Saab, & Kubzansky, 2005).…”
Section: Introductionmentioning
confidence: 55%
“…Genotyping of the 5-HTR2C G68C nonsynonymous (Ser23Cys) polymorphism (rs6318) was carried out using a modified version of a method described by Lappalainen et al (1995b). Research indicates that the Ser 23 allele is constitutively more active than the Cys 23 allele, with allele-specific analysis of receptor function showing functional differences in the activity of the Ser 23 minor allele relative to the Cys 23 allele (Brummett et al 2013). …”
Section: Candidate Gene Selectionmentioning
confidence: 99%
“…Од-нако у психологически здоровых людей с генотипом ТТ гена 5-HT2A (T102C) выявлена повышенная скорость свя-зывания тромбоцитов [30], которая зарегистрирована и у лиц с депрессивными расстройствами [63]. Кроме этого, в недавно выполненном крупном исследовании обнаруже-но, что аллель Ser23C гена 5HT2C (полиморфизм rs6318) связан с тяжестью ИБС, а также с повышенным риском смерти от всех причин, в том числе ИМ [11].…”
Section: работы по изучению связи генотипов гена 5-httunclassified
“…Также на уровне тенденции определяются раз-личия по уровню личностной тревоги между генотипами AG (47,11) и АА (44,1) (p=0,078), а также между генотипа-ми AG (47,11) и GG (44,67) (p=0,072).…”
Section: результатыunclassified